Detailed Description
Hereinafter, the present invention will be described in detail by being divided into 1) a resin composition, 2) a sealing sheet, and 3) a sealing body.
1) Resin composition
The resin composition of the present invention contains the following components (A), (B) and (C):
(A) The components are as follows: modified polyolefin resin
(B) The components are as follows: compounds having cyclic ether groups
(C) The components are as follows: a photo-cationic polymerization initiator.
[ (A) component: modified polyolefin resin
The resin composition of the present invention contains a modified polyolefin resin as the component (A).
By containing the modified polyolefin resin, a resin composition having more excellent sheet processability (film forming property) and a cured product of the resin composition having more excellent adhesive strength can be obtained. In addition, by using a resin composition containing a modified polyolefin resin, an adhesive layer having a thickness described later can be efficiently formed.
The modified polyolefin resin is a polyolefin resin having functional groups introduced therein, which is obtained by modifying a polyolefin resin as a precursor with a modifier.
The polyolefin resin refers to a polymer containing a repeating unit derived from an olefin-based monomer. The polyolefin resin may be a polymer composed of only 1 or 2 or more kinds of repeating units derived from an olefin monomer, or may be a polymer composed of repeating units derived from an olefin monomer and repeating units derived from another monomer copolymerizable with the olefin monomer.
The olefin monomer is preferably an α -olefin having 2 to 8 carbon atoms, more preferably ethylene, propylene, 1-butene, isobutylene or 1-hexene, and still more preferably ethylene or propylene.
Examples of the other monomer copolymerizable with the olefin monomer include vinyl acetate, (meth) acrylate, and styrene. Here, "(meth) acrylic" means acrylic acid or methacrylic acid (hereinafter the same).
Examples of the polyolefin resin include Very Low Density Polyethylene (VLDPE), low Density Polyethylene (LDPE), medium Density Polyethylene (MDPE), high Density Polyethylene (HDPE), linear Low Density Polyethylene (LLDPE), polypropylene (PP), ethylene-propylene copolymer, olefin elastomer (TPO), ethylene-vinyl acetate copolymer (EVA), ethylene- (meth) acrylic acid copolymer, and ethylene- (meth) acrylic acid ester copolymer.
The modifier used in the modification treatment of the polyolefin resin is a compound having a functional group in the molecule.
Examples of the functional group include a carboxyl group, a carboxylic anhydride group, a carboxylic ester group, a hydroxyl group, an epoxy group, an amide group, an ammonium group, a nitrile group, an amino group, an imide group, an isocyanate group, an acetyl group, a thiol group, an ether group, a thioether group, a sulfo group, a phosphine group, a nitro group, a urethane group, an alkoxysilyl group, a silanol group, and a halogen atom. Among them, carboxyl group, carboxylic anhydride group, carboxylic ester group, hydroxyl group, ammonium group, amino group, imide group, isocyanate group, alkoxysilyl group are preferable, carboxylic anhydride group and alkoxysilyl group are more preferable, and carboxylic anhydride group is particularly preferable.
The compound having a functional group may have 2 or more functional groups in the molecule.
Examples of the modified polyolefin resin include an acid-modified polyolefin resin and a silane-modified polyolefin resin, and from the viewpoint of obtaining the more excellent effect of the present invention, the acid-modified polyolefin resin is preferable.
The acid-modified polyolefin resin is a substance obtained by graft-modifying a polyolefin resin with an acid. For example, an unsaturated carboxylic acid is reacted with a polyolefin resin, and a carboxyl group is introduced (graft modification). In the present specification, the term "acid" includes the term "acid anhydride" and the term "unsaturated carboxylic acid" includes the term "unsaturated carboxylic acid anhydride" and the term "carboxyl" includes the term "carboxylic acid anhydride".
Examples of the unsaturated carboxylic acid that reacts with the polyolefin resin include maleic acid, fumaric acid, itaconic acid, citraconic acid, glutaconic acid, tetrahydrophthalic acid, aconitic acid, maleic anhydride, itaconic anhydride, glutaconic anhydride, citraconic anhydride, aconitic anhydride, norbornene dianhydride, tetrahydrophthalic anhydride, and the like.
They may be used alone or in combination of 1 or more than 2. Among them, maleic anhydride is preferable because it is easy to obtain a resin composition having more excellent sheet processability (film forming property) and a cured product of the resin composition having more excellent adhesive strength.
The amount of the unsaturated carboxylic acid to be reacted with the polyolefin resin is preferably 0.1 to 5 parts by mass, more preferably 0.2 to 3 parts by mass, and still more preferably 0.2 to 1 part by mass per 100 parts by mass of the polyolefin resin. The resin composition containing the acid-modified polyolefin resin thus obtained can easily give a cured product having more excellent adhesive strength.
As the acid-modified polyolefin resin, commercially available ones can be used. Examples of the commercial products include Admer (registered trademark) (manufactured by mitsubishi chemical company), unicole (registered trademark) (manufactured by mitsubishi chemical company), bondyRam (manufactured by polybam company), orevac (registered trademark) (manufactured by arcema company), and Modic (registered trademark) (manufactured by mitsubishi chemical company).
The silane-modified polyolefin resin is a polyolefin resin obtained by graft modification of a polyolefin resin with an unsaturated silane compound. The silane-modified polyolefin resin has a structure in which an unsaturated silane compound as a side chain is graft-copolymerized to a polyolefin resin as a main chain. For example, a silane-modified polyethylene resin and a silane-modified ethylene-vinyl acetate copolymer are exemplified, and a silane-modified polyethylene resin such as a silane-modified low density polyethylene, a silane-modified ultra low density polyethylene, a silane-modified linear low density polyethylene or the like is preferable.
As the unsaturated silane compound that reacts with the above polyolefin resin, a vinyl silane compound is preferable. Examples of the vinylsilane compound include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltripropoxysilane, vinyltriisopropoxysilane, vinyltributoxysilane, vinyltripentoxysilane, vinyltriphenoxysilane, vinyltribenzyloxy silane, vinyltrimethylene dioxysilane, vinyltriethylene dioxysilane, vinylpropionyloxy silane, vinyltriacetoxy silane, and vinyltricarboxyl silane.
They may be used alone or in combination of 1 or more than 2.
The conditions in the case of graft-polymerizing an unsaturated silane compound on a polyolefin resin as a main chain may be a conventional method of known graft polymerization.
The amount of the unsaturated silane compound to be reacted with the polyolefin resin is preferably 0.1 to 10 parts by mass, more preferably 0.3 to 7 parts by mass, and still more preferably 0.5 to 5 parts by mass, relative to 100 parts by mass of the polyolefin resin. The resin composition containing the silane-modified polyolefin resin thus obtained can easily give a cured product having more excellent adhesive strength.
As the silane-modified polyolefin-based resin, commercially available ones can be used. Examples of the commercial products include Linklon (registered trademark) (manufactured by mitsubishi chemical company). Among them, low-density polyethylene-based Linklon, linear low-density polyethylene-based Linklon, ultra-low-density polyethylene-based Linklon, and ethylene-vinyl acetate copolymer-based Linklon can be preferably used.
The modified polyolefin resin may be used alone or in combination of 1 or more than 2.
The modified polyolefin resin preferably has a number average molecular weight (Mn) of 10,000 to 2,000,000, more preferably 20,000 to 1,500,000.
The number average molecular weight (Mn) of the modified polyolefin resin can be obtained as a standard polystyrene conversion value by Gel Permeation Chromatography (GPC) using Tetrahydrofuran (THF) as a solvent.
[ (B) component: compounds having cyclic ether groups
The resin composition of the present invention contains a compound having a cyclic ether group as the component (B).
Since the compound having a cyclic ether group is excellent in compatibility with the component (a), a resin composition excellent in sheet processability (film forming property) and a cured product of the resin composition excellent in colorless transparency and water vapor blocking property can be obtained by using the compound.
Examples of the cyclic ether group include an oxirane group (epoxy group), an oxetanyl group (oxetanyl group), a tetrahydrofuranyl group, and a tetrahydropyranyl group.
The compound having a cyclic ether group means a compound having at least 1 cyclic ether group in the molecule. Among them, a compound having an oxirane group or an oxetane group is preferable, and a compound having 2 or more oxirane groups or oxetane groups in the molecule is particularly preferable, from the viewpoint that a resin composition having more excellent sheet processability (film forming property) and a cured product of a resin composition having more excellent adhesive strength can be obtained.
Examples of the compound having an oxirane group in the molecule include aliphatic epoxy compounds (excluding alicyclic epoxy compounds), aromatic epoxy compounds, and alicyclic epoxy compounds.
The aliphatic epoxy compounds include:
a monofunctional epoxy compound such as a glycidyl ether of an aliphatic alcohol or a glycidyl ester of an alkyl carboxylic acid,
polyfunctional epoxy compounds such as polyglycidyl ethers of aliphatic polyols or alkylene oxide adducts, polyglycidyl esters of aliphatic long-chain polybasic acids, and epoxy compounds having a triazine skeleton.
Representative examples of these aliphatic epoxy compounds include:
allyl glycidyl ether, butyl glycidyl ether, 2-ethylhexyl glycidyl ether, C12-13 mixed alkyl glycidyl ether, 1, 4-butanediol diglycidyl ether, neopentyl glycol diglycidyl ether, triglycidyl ether of glycerol, triglycidyl ether of trimethylolpropane, tetraglycidyl ether of sorbitol, hexaglycidyl ether of dipentaerythritol, diglycidyl ether of polyethylene glycol, diglycidyl ether of polypropylene glycol, diglycidyl ether of dicyclopentadiene dimethanol, or polyglycidyl ether of polyether polyol obtained by adding 1 or more alkylene oxides to aliphatic polyhydric alcohols such as propylene glycol, trimethylolpropane, glycerol, diglycidyl esters of aliphatic long-chain dibasic acids;
Monoglycidyl ethers of aliphatic higher alcohols or glycidyl esters of higher fatty acids, epoxidized soybean oil, octyl epoxystearate, butyl epoxystearate, epoxidized polybutadiene;
2,4, 6-tris (glycidoxy) -1,3, 5-triazine, and the like.
Further, as the aliphatic epoxy compound, commercially available ones can be used. The commercial products include:
denacol EX-121, denacol EX-171, denacol EX-192, denacol EX-211, denacol EX-212, denacol EX-313, denacol EX-314, denacol EX-321, denacol EX-411, denacol EX-421, denacol EX-512, denacol EX-521, denacol EX-611, denacol EX-612, denacol EX-614, denacol EX-622, denacol EX-810, denacol EX-811, denacol EX-850, denacol EX-851, denacol EX-821, denacol EX-830, denacol EX-832, denacol EX-841, denacol EX-861, denacol EX-931, denacol EX-941, denacol EX-920, denacol EX-Nagase ChemteX Corporation above,
epoligo M-1230, epoligo 40E, epolight 100E, epolight 200E, epolight 400E, epolight 70P, epolight 200P, epolight 400P, epolight 1500NP, epoligo 1600, epoligo 80MF, epoligo 100MF (manufactured by Kyoro chemical Co., ltd.),
ADEKA GLYCILOL ED-503, ADEKA GLYCILOL ED-503G, ADEKA GLYCILOL ED-506, ADEKA GLYCILOL ED-523T, ADEKA RESIN EP-4088S, ADEKA RESIN EP-4088L, ADEKA RESIN EP-4080E (made by ADEKA Co., ltd.),
TEPIC-FL, TEPIC-PAS, TEPIC-UC (the above are manufactured by daily chemical company), and the like.
Examples of the aromatic epoxy compound include a polyhydric phenol having at least 1 aromatic ring such as phenol, cresol and butylphenol, and a mono/polyglycidyl etherate of an alkylene oxide adduct thereof.
Representative examples of these aromatic epoxy compounds include:
glycidyl ethers of bisphenol A, bisphenol F or compounds obtained by further adding alkylene oxide thereto or epoxy novolac resins,
mono/polyglycidyl ethers of aromatic compounds having 2 or more phenolic hydroxyl groups such as resorcinol, hydroquinone and catechol,
glycidyl ethers of aromatic compounds having at least 2 alcoholic hydroxyl groups such as phenyldimethanol, phenyldiethanol and phenyldibutyl alcohol,
glycidyl esters of polybasic acid aromatic compounds having 2 or more carboxylic acids such as phthalic acid, terephthalic acid, and trimellitic acid, glycidyl esters of benzoic acid, and epoxides of styrene oxide or divinylbenzene.
Further, as the aromatic epoxy compound, a commercially available product can be used. The commercial products include:
denacol EX-146, denacol EX-147, denacol EX-201, denacol EX-203, denacol EX-711, denacol EX-721, oncoat EX-1020, oncoat EX-1030, oncoat EX-1040, oncoat EX-1050, oncoat EX-1051, oncoat EX-1010, oncoat EX-1011, oncoat 1012 (manufactured by Nagase ChemteX Corporation above),
OGSOL PG-100, OGSOL EG-200, OGSOL EG-210, OGSOL EG-250 (manufactured by Ltd.; osaka Gas Chemicals Co.; above),
HP4032, HP4032D, HP4700 (the above is manufactured by DIC Co.),
ESN-475V (above is made by Nippon Kagaku Co., ltd.),
JER (original EPIKOTE) YX8800 (Mitsubishi chemical corporation),
marproof G-0105SA, marproof G-0130SP (manufactured by Nikko Co., ltd.),
EPICLON N-665, EPICLON HP-7200 (the above is manufactured by DIC Co.),
EOCN-1020, EOCN-102S, EOCN-103S, EOCN-104S, XD-1000, NC-3000, EPPN-501H, EPPN-501HY, EPPN-502H, NC-7000L (manufactured by Japanese chemical Co., ltd.),
ADEKA RESIN EP-4000, ADEKA RESIN EP-4005, ADEKA RESIN EP-4100, ADEKA RESIN EP-4901 (made by ADEKA Co., ltd.),
TECHMORE VG-3101L (PRINTEC. Above), and the like.
Examples of the alicyclic epoxy compound include polyglycidyl ethers of polyhydric alcohols having at least 1 alicyclic structure, and cyclohexene oxide or cyclopentene oxide-containing compounds obtained by epoxidizing a cyclohexene or cyclopentene ring-containing compound with an oxidizing agent.
Representative examples of the alicyclic epoxy compounds include hydrogenated bisphenol A diglycidyl ether, 3, 4-epoxycyclohexylmethyl-3, 4-epoxycyclohexylformate, 3, 4-epoxy-1-methylcyclohexyl-3, 4-epoxy-1-methylhexylformate, 6-methyl-3, 4-epoxycyclohexylmethyl-6-methyl-3, 4-epoxycyclohexylformate, 3, 4-epoxy-3-methylcyclohexylmethyl-3, 4-epoxy-3-methylcyclohexylformate, 3, 4-epoxy-5-methylcyclohexylmethyl-3, 4-epoxy-5-methylcyclohexylformate, bis (3, 4-epoxycyclohexylmethyl) adipate, 3, 4-epoxy-6-methylcyclohexylformate, methylenebis (3, 4-epoxycyclohexane), propane-2, 2-diyl-bis (3, 4-epoxycyclohexane), 2-bis (3, 4-epoxycyclohexyl) propane, dicyclopentadiene di (3, 4-epoxycyclohexane) epoxide, ethylene-bis (3, 4-epoxycyclohexane) oxide, and 2-epoxycyclohexane-2-ethyl-phthalate.
Further, as the alicyclic epoxy compound, a commercially available compound can be used. Commercially available products include Celloxide 2021P, celloxide 2081, celloxide 2000, celloxide 3000 (manufactured by Daicel Corporation), and the like.
Examples of the compound having an oxetanyl group in the molecule include difunctional aliphatic oxetane compounds such as 3, 7-bis (3-oxetanyl) -5-oxa-nonane, 1, 4-bis [ (3-ethyl-3-oxetanylmethoxy) methyl ] benzene, 1, 2-bis [ (3-ethyl-3-oxetanylmethoxy) methyl ] ethane, 1, 3-bis [ (3-ethyl-3-oxetanylmethoxy) methyl ] propane, ethylene glycol bis (3-ethyl-3-oxetanylmethyl) ether, triethylene glycol bis (3-ethyl-3-oxetanylmethyl) ether, tetraethylene glycol bis (3-ethyl-3-oxetanylmethyl) ether, 1, 4-bis (3-ethyl-3-oxetanylmethoxy) butane, 1, 6-bis (3-ethyl-3-oxetanylmethoxy) hexane, 3-ethyl-3- [ (phenoxymethyl) oxetane, 3-ethyl-3- (hexyloxymethyl) oxetane, 3-ethyl-3- (2-oxetanylmethyl) oxetane, 3-oxetane and 3-hydroxy-methyl-oxetane And monofunctional oxetane compounds such as 3-ethyl-3- (chloromethyl) oxetane.
As the compound having an oxetanyl group in the molecule, a commercially available product can be used. The commercial products include:
2-hydroxyethyl vinyl ether, diethylene glycol monovinyl ether, 4-hydroxybutyl vinyl ether (manufactured by Wash petrochemistry Co., ltd.),
ARON OXETANE OXT-121, OXT-221, EXOH, POX, OXA, OXT-101, OXT-211, OXT-212 (manufactured by east Asia Synthesis Co., ltd.),
ETERNACOLL OXBP, OXTP (the above is manufactured by the company of encyclopedia of the usa) and the like.
Among these compounds having a cyclic ether group, those which are liquid at 25 ℃ are preferable from the viewpoint of obtaining a resin composition having more excellent sheet processability (film forming property) and a cured product of the resin composition having more excellent adhesive strength. In addition, a substance in which the cyclic ether group is an ethylene oxide group is preferable.
The molecular weight of the compound having a cyclic ether group is usually 700 to 5000, preferably 1200 to 4000.
The cyclic ether equivalent of the compound having a cyclic ether group is preferably 100g/eq or more and 500g/eq or less, more preferably 150g/eq or more and 300g/eq or less.
By using a resin composition having a cyclic ether equivalent of a compound having a cyclic ether group in the above range, a sealing material having high adhesive strength and excellent curability can be effectively produced.
These compounds having a cyclic ether group may be used singly or in combination of 1 or more than 2.
The cyclic ether equivalent in the present invention means a value obtained by dividing the molecular weight by the number of cyclic ethers.
The content of the compound having a cyclic ether group is preferably 5 to 50 parts by mass, more preferably 5 to 40 parts by mass, and still more preferably 5 to 25 parts by mass, per 100 parts by mass of the component (a).
By setting the content of the compound having a cyclic ether group to the above range, a cured product of the resin composition having more excellent adhesive strength can be easily obtained.
[ (C) component: photo cationic polymerization initiator ]
The resin composition of the present invention contains a photo-cationic polymerization initiator as the component (C).
The photo-cation polymerization initiator is a compound that initiates a curing reaction of a cationically curable compound by generating a cation species by irradiation with light, and is composed of a cation portion that absorbs light and an anion portion that is an acid generation source.
Examples of the photo-cation polymerization initiator include sulfonium salt compounds, iodonium salt compounds, phosphonium salt compounds, ammonium salt compounds, antimonate salt compounds, diazonium salt compounds, selenate compounds, oxonium salt compounds, and bromonium salt compounds. Among them, the sulfonium salt-based compound is preferable, and the aromatic sulfonium salt-based compound having an aromatic group is more preferable, from the viewpoint of excellent compatibility with the component (B) and excellent storage stability of the obtained resin composition.
Examples of sulfonium salt compounds include triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, triphenylsulfonium tetrakis (pentafluorophenyl) borate, 4' -bis [ diphenylsulfonium ] diphenyl sulfide-bis hexafluorophosphate, 4' -bis [ bis (. Beta. -hydroxyethoxy) phenylsulfonium ] diphenyl sulfide-bis hexafluoroantimonate, 7- [ bis (p-toluoyl) sulfonium ] -2-isopropylthioxanthone hexafluorophosphate, 7- [ bis (p-toluoyl) sulfonium ] -2-isopropylthioxanthone hexafluoroantimonate, 7- [ bis (p-toluoyl) sulfonium ] -2-isopropyltetrakis (pentafluorophenyl) borate, phenylcarbonyl-4 ' -diphenylsulfonium-diphenyl sulfide-hexafluorophosphate, phenylcarbonyl-4 ' -diphenylsulfonium-diphenyl sulfide-hexafluoroantimonate, 4-t-butylphenylcarbonyl-4 ' -diphenylsulfonium-hexafluorohexa-4 ' -diphenylsulfonium-hexafluorophosphate, 7- [ bis (p-toluoyl) sulfonium ] -2-isopropylthioxanthone hexafluoroantimonate, 7- [ bis (p-toluoyl) sulfonium ] -2-isopropyltetrakis (pentafluorophenyl) borate, phenylcarbonyl-4 ' -diphenylsulfonium-hexafluoroantimonate, 4-t-butylphenylcarbonyl-4 ' -diphenylsulfonium-diphenylsulfide-hexafluoroantimonate, 4-t-butylphenylcarbonyl-4 ' -diphenylsulfonium hexafluoroantimonate, 4-t-butylphenyl sulfide-diphenylsulfonium, halides of thiophenyl diphenyl sulfonium hexafluoroantimonate, 4 '-tris (. Beta. -hydroxyethoxyphenyl) sulfonium hexafluoroantimonate, 4' -bis [ diphenyl sulfonium ] diphenyl sulfide-bis hexafluoroantimonate, diphenyl [4- (phenylsulfanyl) phenyl ] sulfonium trifluorotris (pentafluoroethyl) phosphate, tris [4- (4-acetylphenylsulfanyl) phenyl ] sulfonium tris [ (trifluoromethyl) sulfonyl ] methanation, and the like.
Examples of the iodonium salt compound include diphenyliodonium tetrakis (pentafluorophenyl) borate, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, bis (4-nonylphenyl) iodonium hexafluorophosphate, (triscumyl) iodonium tetrakis (pentafluorophenyl) borate, and the like.
Examples of the phosphonium salt compound include tri-n-butyl (2, 5-dihydroxyphenyl) phosphonium bromide and cetyl tributyl phosphonium chloride.
Examples of the ammonium salt compound include benzyltrimethylammonium chloride, phenyltributylammonium chloride, and benzyltrimethylammonium bromide.
Examples of the antimonate-based compound include triphenylsulfonium hexafluoroantimonate, p- (phenylsulfanyl) phenyldiphenylsulfonium hexafluoroantimonate, 4-chlorophenyl diphenylsulfonium hexafluoroantimonate, bis [4- (diphenylsulfonium) phenyl ] sulfide bis hexafluoroantimonate, and diallyl iodonium hexafluoroantimonate.
These photo-cationic polymerization initiators may be used alone in 1 kind, or in combination of 2 or more kinds.
Further, as the photo cation polymerization initiator, commercially available ones can be used. As commercial products, there may be mentioned CYRACURE UVI-6970, CYRACURE UVI-6974, CYRACURE UVI-6990, CYRACURE UVI-950 (manufactured by Union Carbide Corporation above), irgacure 250, irgacure 261, irgacure 264 (manufactured by Ciba Specialty Chemicals Inc. above), SP-150, SP-151, SP-170, OPTOMER SP-171 (manufactured by ADEKA Co., above), CG-24-61 (manufactured by Ciba Specialty Chemicals Inc. above), DAICAT II (manufactured by Daicel Corporation), UVAC1590, UVAC1591 (manufactured by Daicel-Cytec Co., above), ltd., CI-2064, CI-2639, CI-2624, CI-2481, CI-2734, CI-2855, CI-2823, CI-2758, CIT-1682 (manufactured by Japan Caesada, supra), PI-2074 (manufactured by Rhodia, supra), FFC509 (manufactured by 3M), BBI-102, BBI-101, BBI-103, MPI-103, TPS-103, MDS-103, DTS-103, NAT-103, NDS-103 (manufactured by Midori Kagaku Co., ltd., supra), CD-1010, CD-1011, CD-1012 (manufactured by Sartomer, supra), CPI-100P, CPI-101A, CPI-200K, CPI-310B (manufactured by San-Apro Ltd., supra), and the like.
The content of the photo-cation polymerization initiator is usually 0.02 to 2 parts by mass, preferably 0.03 to 1 part by mass, more preferably 0.04 to 0.5 part by mass, per 100 parts by mass of the component (B).
By setting the content of the photo-cation polymerization initiator to the above range, a cured product of the resin composition having more excellent adhesive strength can be easily obtained.
If the content of the photo cation polymerization initiator is too large, the elastic modulus after curing may be excessively increased, and the adhesive strength of the cured product of the resin composition may be lowered.
The resin composition of the present invention may further contain components other than the component (A), the component (B) and the component (C).
Examples of the components other than the component (a), the component (B) and the component (C) include a tackifier, a silane coupling agent, a solvent and the like.
Examples of the thickener include:
rosin resins such as rosin resins, rosin ester resins, and rosin-modified phenolic resins, and hydrogenated rosin resins obtained by hydrogenating these rosin resins;
terpene resins such as terpene resins, aromatic modified terpene resins, and terpene phenol resins, and hydrogenated terpene resins obtained by hydrogenating these terpene resins;
styrene resins such as α -methylstyrene homo-resin, α -methylstyrene/styrene copolymer resin, styrene monomer/aliphatic monomer copolymer resin, styrene monomer/α -methylstyrene/aliphatic monomer copolymer resin, styrene monomer homo-resin, and styrene monomer/aromatic monomer copolymer resin, hydrogenated styrene resins obtained by hydrogenating these styrene resins;
A C5-series petroleum resin obtained by copolymerizing a C5 fraction such as pentene, isoprene, piperine, or 1, 3-pentadiene produced by thermal decomposition of naphtha, and a hydrogenated petroleum resin of the C5-series petroleum resin;
and C9-based petroleum resins obtained by copolymerizing C9 fractions such as indene and vinyl toluene produced by thermal decomposition of naphtha, hydrogenated petroleum resins of the C9-based petroleum resins, and the like. Among them, a styrene-based resin is preferable, and a styrene-based monomer/aliphatic monomer copolymer-based resin is more preferable.
These tackifiers may be used singly or in combination of 1 or more than 2.
The tackifier may be a commercially available one. The commercial products include:
terpene resins such as YS Resin P and A series, CLEARON (registered trademark) P series (YASUHARA CHEMICAL CO., LTD.), piccolyte A and C series (PINOVA Co.);
aliphatic petroleum resins such as the Quintone (registered trademark) A, B, R, CX series (manufactured by Zeon Corporation);
styrene resins such as FTR (registered trademark) series (manufactured by mitsunobu chemical company);
alicyclic petroleum resins such as ARKON P and M series (manufactured by Kunchuan chemical Co., ltd.), ESCOREZ (registered trademark) series (manufactured by ExxonMobil Chemical Company), EASTOTAC (registered trademark) series (manufactured by Eastman Chemical Company), IMARV (registered trademark) series (manufactured by Kunzhong Co., ltd.);
Foral series (manufactured by PINOVA corporation), PENSEL (registered trademark) A series, ESTER gum, SUPER ESTER, pin Crystal (registered trademark) (manufactured by Sichuan chemical industry Co., ltd.) and the like.
The weight average molecular weight of the tackifier is preferably 100 to 10,000, more preferably 500 to 5,000, from the viewpoint of imparting excellent adhesion.
The softening point of the tackifier is preferably 50 to 160 ℃, more preferably 60 to 140 ℃, and even more preferably 70 to 130 ℃ from the viewpoint of imparting excellent adhesion.
When the resin composition of the present invention contains a tackifier, the content thereof is preferably 1 to 200 parts by mass, more preferably 10 to 150 parts by mass, per 100 parts by mass of the component (a).
By setting the content of the tackifier to the above range, a cured product of the resin composition having more excellent adhesive strength can be easily obtained.
The silane coupling agent may be:
silane coupling agents having a (meth) acryloyl group such as 3-methacryloxypropyl methyl dimethoxy silane, 3-methacryloxypropyl trimethoxy silane, 3-methacryloxypropyl methyl diethoxy silane, 3-methacryloxypropyl triethoxy silane, 3-acryloxypropyl trimethoxy silane,
Silane coupling agents having a vinyl group such as vinyltrimethoxysilane, vinyltriethoxysilane, dimethoxymethylvinylsilane, diethoxymethylvinylsilane, trichlorovinylsilane, and vinyltris (2-methoxyethoxy) silane,
silane coupling agents having an epoxy group such as 2- (3, 4-epoxycyclohexyl) ethyltrimethoxysilane, 3-glycidoxypropyl trimethoxysilane, 3-glycidoxypropyl methyldiethoxysilane, and 3-glycidoxypropyl triethoxysilane,
a silane coupling agent having a styrene group such as p-styryltrimethoxysilane or p-styryltriethoxysilane,
silane coupling agents having an amino group such as hydrochloride salts of N- (2-aminoethyl) -3-aminopropyl methyldimethoxy silane, N- (2-aminoethyl) -3-aminopropyl trimethoxy silane, N- (2-aminoethyl) -3-aminopropyl triethoxy silane, 3-aminopropyl trimethoxy silane, 3-triethoxysilyl-N- (1, 3-dimethylbutylidene) propylamine, N-phenyl-3-aminopropyl trimethoxy silane, N- (vinylbenzyl) -2-aminoethyl-3-aminopropyl trimethoxy silane,
Silane coupling agents having an ureido group such as 3-ureidopropyltrimethoxysilane and 3-ureidopropyltriethoxysilane,
silane coupling agents having halogen atoms such as 3-chloropropyl trimethoxysilane and 3-chloropropyl triethoxysilane,
a mercapto silane coupling agent such as 3-mercaptopropyl methyl dimethoxy silane and 3-mercaptopropyl trimethoxy silane,
silane coupling agents having a thioether group such as bis (trimethoxysilylpropyl) tetrasulfide and bis (triethoxysilylpropyl) tetrasulfide,
silane coupling agents having an isocyanate group such as 3-isocyanatopropyl trimethoxysilane and 3-isocyanatopropyl triethoxysilane,
allyl silane coupling agents such as allyl trichlorosilane, allyl triethoxysilane, and allyl trimethoxysilane,
and silane coupling agents having a hydroxyl group such as 3-hydroxypropyl trimethoxysilane and 3-hydroxypropyl triethoxysilane.
These silane coupling agents may be used alone or in combination of 1 or more than 2.
When the resin composition of the present invention contains a silane coupling agent, the content thereof is preferably 0.01 to 10 parts by mass, more preferably 0.02 to 5 parts by mass, relative to 100 parts by mass of the component (a).
By setting the content of the silane coupling agent to the above range, a cured product of the resin composition having more excellent adhesive strength can be easily obtained.
The solvent may be:
aliphatic hydrocarbon solvents such as n-hexane and n-heptane,
aromatic hydrocarbon solvents such as toluene and xylene,
halogenated hydrocarbon solvents such as methylene chloride, vinyl chloride, chloroform, carbon tetrachloride, 1, 2-dichloroethane, monochlorobenzene and the like,
alcohol solvents such as methanol, ethanol, propanol, butanol, propylene glycol monomethyl ether and the like,
ketone solvents such as acetone, methyl ethyl ketone, 2-pentanone, isophorone and cyclohexanone,
an ester solvent such as ethyl acetate or butyl acetate,
cellosolve solvents such as ethyl cellosolve,
ether solvents such as 1, 3-dioxolane, and the like.
These solvents may be used alone or in combination of 1 or more than 2. The content of the solvent may be appropriately determined in consideration of coatability, film thickness, and the like.
The resin composition of the present invention may contain components other than the tackifier, the silane coupling agent and the solvent within a range that does not hinder the effects of the present invention.
Examples of the components other than the thickener, the silane coupling agent and the solvent include an antistatic agent, a stabilizer, an antioxidant, a plasticizer, a lubricant, a coloring pigment, and the like. Their contents may be appropriately determined according to the purpose.
The resin composition of the present invention can be prepared by appropriately mixing and stirring the prescribed components according to a conventional method.
2) Sealing sheet
The sealing sheet of the present invention is the following sealing sheet (α), sealing sheet (β) or sealing sheet (γ).
Sealing sheet (α): a sealing sheet comprising a substrate or a release film and an adhesive layer formed on the substrate or the release film, wherein the adhesive layer is formed using the resin composition of the present invention.
Sealing sheet (β): and a sealing sheet comprising 2 sheets of release film and an adhesive layer sandwiched between the 2 sheets of release film, wherein the adhesive layer is formed using the resin composition of the present invention.
Sealing sheet (γ): and a sealing sheet comprising a release film, a gas barrier film, and an adhesive layer sandwiched between the release film and the gas barrier film, wherein the adhesive layer is formed using the resin composition of the present invention.
The seal sheets are in a state before use, and when the seal sheet of the present invention is used, the release film is usually peeled off.
As a base material constituting the sealing sheet (α), a resin film is generally used.
Examples of the resin component of the resin film include polyimide, polyamide, polyamideimide, polyphenylene ether, polyether ketone, polyether ether ketone, polyolefin, polyester, polycarbonate, polysulfone, polyether sulfone, polyphenylene sulfide, polyarylate, acrylic resin, cycloolefin polymer, aromatic polymer, and urethane polymer.
The thickness of the base material is not particularly limited, but is preferably 10 to 500 μm, more preferably 10 to 300 μm, and even more preferably 15 to 200 μm from the viewpoint of heat shrinkage or versatility of the adhesive layer in the drying step.
The release film constituting the sealing sheet (α) functions as a support in the step of producing the sealing sheet (α), and functions as a protective sheet for the adhesive layer until the sealing sheet (α) is used.
As the release film, a conventionally known material can be used. For example, a release film having a release layer obtained by a release treatment with a release agent on a release film substrate can be exemplified.
Examples of the base material for a release film include paper base materials such as cellophane, coated paper, and high-quality paper, and laminated paper in which a thermoplastic resin such as polyethylene is laminated on these paper base materials, plastic films such as polyethylene terephthalate resin, polybutylene terephthalate resin, polyethylene naphthalate resin, polypropylene resin, and polyethylene resin, and the like.
Examples of the release agent include rubber-based elastomers such as silicone-based resins, olefin-based resins, isoprene-based resins, and butadiene-based resins, long-chain alkyl-based resins, alkyd-based resins, and fluorine-based resins.
The thickness of the release film is not particularly limited, and is usually about 20 to 250. Mu.m.
The method for producing the sealing sheet (α) is not particularly limited. For example, the sealing sheet (α) may be prepared by a casting method.
In the case of preparing the sealing sheet (α) by the casting method, the resin composition of the present invention may be applied to a release layer surface of a base material or a release film subjected to a release treatment by a known method, and the obtained coating film is dried to obtain the sealing sheet (α).
Examples of the method for coating the resin composition include spin coating, spray coating, bar coating, doctor blade coating, roll coating, blade coating, die coating, and gravure coating.
The method of drying the coating film includes conventionally known drying methods such as hot air drying, hot roll drying, and infrared irradiation.
The conditions for drying the coating film are, for example, 80 to 150 ℃ for 30 seconds to 5 minutes.
The adhesive layer of the sealing sheet (α) can be formed by photocuring a coating film formed using the resin composition of the present invention.
The conditions at the time of photocuring are not particularly limited. The adhesive layer may be photo-cured by irradiation of active energy rays such as ultraviolet rays, visible rays, X-rays, electron beams, and the like.
In the present invention, from the viewpoint of obtaining a sealing sheet excellent in transparency, it is preferable to use light curing by irradiation of ultraviolet rays.
Specific examples of the ultraviolet source for irradiating ultraviolet rays include light sources such as an ultra-high pressure mercury lamp, a low pressure mercury lamp, a carbon arc lamp, a black fluorescent lamp, and a metal halide lamp. The wavelength of the irradiated ultraviolet light may be 190 to 380 nm.
The irradiation amount of ultraviolet rays is preferably 50-1000 mW/cm 2 The light quantity is 50-1000 mJ/cm 2 Left and right.
The irradiation time of the ultraviolet ray is usually 0.1 to 1000 seconds, preferably about 1 to 500 seconds.
The thickness of the adhesive layer of the sealing sheet (alpha) is usually 1 to 50 μm, preferably 5 to 30 μm. An adhesive layer having a thickness within the above range is suitable for use as a sealing material.
The thickness of the adhesive layer can be measured according to JIS K7130 (1999) using a known thickness meter.
The adhesive layer of the sealing sheet of the present invention has excellent adhesive strength.
When 180 DEG peel test is performed at a temperature of 23 ℃ and a relative humidity of 50%, the adhesive strength of the adhesive layer is usually 1 to 20N/25mm, preferably 2.5 to 15N/25mm. The 180 ° peel test can be measured by the method described in the examples.
The adhesive layer of the sealing sheet of the present invention is excellent in colorless transparency.
The total light transmittance of the adhesive layer having a thickness of 20 μm after the photo-curing treatment is preferably 85% or more, more preferably 90% or more. The total light transmittance is not particularly limited, but is usually 95% or less.
As described above, in the resin composition of the present invention, the modified polyolefin-based resin is used as the component (a), and the compound having a cyclic ether group having high compatibility with the component (a) is further used as the component (B). Therefore, the adhesive layer of the sealing sheet of the present invention has high total light transmittance. The total light transmittance can be measured by the method described in examples.
In addition, when an adhesive layer having a thickness of 20 μm obtained by the photo-curing treatment is measured, the value of L in the CIE1976L a b color system defined in JIS Z8781-4 (2013) is 90 to 98. In addition, a is-2 to 2. In addition, b is-2 to 2.
In the l×a×b color system, l×represents brightness, and a and b×represent hue and chroma. The color and chromaticity in the red direction are represented by positive values of a, the color and chromaticity in the green direction are represented by negative values of a, the color and chromaticity in the yellow direction are represented by positive values of b, and the color and chromaticity in the blue direction are represented by negative values of b. The absolute values of a and b become colorless as they become smaller.
The L value of the adhesive layer obtained by the photo-curing treatment is preferably 92 to 98, more preferably 94 to 98.
The value of a is usually-2 to 2, preferably-1 to 1, more preferably-0.5 to 0.5.
The value of b is usually-2 to 2, preferably-1 to 1, more preferably-0.5 to 0.5.
The adhesive layer obtained by the photo-curing treatment has small shifts in the red direction (+a), green direction (-a), yellow direction (+b), and blue direction (-b).
The resin composition capable of forming an adhesive layer having a color gamut of L, a, and b in the above-described range is suitable as a sealing material for light emitting devices such as organic EL elements because of high total light transmittance and very little coloring.
Therefore, the sealing sheet of the present invention is suitable for optical applications such as sealing materials for light emitting devices such as organic EL elements.
The value of L a b in the CIE1976L b color system can be determined by the methods described in the examples.
The yellowness index (YI value) of the sealing sheet is usually 0.01 to 2, preferably 0.01 to 1. The yellow index can be determined by the method described in the examples.
The adhesive layer of the sealing sheet of the present invention is excellent in water vapor blocking property.
The water vapor permeability of the adhesive layer having a thickness of 20 μm obtained by the photo-curing treatment is usually 0.1 to 200g/m 2 Preferably 0.1 to 150g/m per day 2 Day. The water vapor permeability can be obtained by the method described in the examplesAnd (5) measuring.
The release film and the adhesive layer constituting the sealing sheet (β) are the same as those shown as the release film and the adhesive layer constituting the sealing sheet (α), respectively.
The 2 release films in the sealing sheet (β) may be the same or different, but it is preferable that the 2 release films have different release forces. The release force by the 2-piece release film is different, and problems are not easy to occur when the sealing piece is used. That is, by varying the peeling force of the 2 sheets of peeling films, the step of peeling the peeling films initially can be performed more effectively.
The method for producing the sealing sheet (β) is not particularly limited.
For example, in the case of preparing the sealing sheet (β) by the casting method, the resin composition of the present invention is coated on the release layer surface of the release film subjected to the release treatment by the same method as that shown in the preparation method of the sealing sheet (α), and the obtained coating film is dried to be photo-cured, whereby an adhesive layer with a release film is prepared, and then another 1 release film is superimposed on the adhesive layer, whereby the sealing sheet (β) can be obtained.
The release film and the adhesive layer constituting the sealing sheet (γ) are the same as those shown as the release film and the adhesive layer constituting the sealing sheet (α) or the sealing sheet (β), respectively.
The gas barrier film constituting the sealing sheet (γ) is not particularly limited as long as it is a film having water vapor blocking property.
The gas barrier film preferably has a water vapor transmission rate of 0.1g/m in an environment where the temperature is 40 ℃ and the relative humidity is 90% (hereinafter abbreviated as "90% RH") 2 Preferably less than or equal to day, more preferably 0.05g/m 2 Preferably 0.005 g/m/day or less 2 And/or less.
The water vapor permeability of the gas barrier film at 40℃and 90% RH was 0.1g/m 2 And/or less, penetration of oxygen, moisture, or the like into the element interior of an organic EL element or the like formed on a substrate can be effectively suppressed, thereby effectively suppressing deterioration of an electrode or an organic layer.
The transmittance of the gas barrier film, such as water vapor, can be measured using a known gas transmittance measuring device.
Examples of the gas barrier film include a metal foil, a thin film glass, and a resin film. Among them, a resin film is preferable, and a gas barrier film having a base material and a gas barrier layer is more preferable.
The resin component constituting the base material may be the same as the resin component of the resin film that can be used as the base material constituting the sealing sheet (α).
The thickness of the base material is not particularly limited, but is preferably 0.5 to 500. Mu.m, more preferably 1 to 200. Mu.m, still more preferably 5 to 100. Mu.m, from the viewpoint of ease of handling.
The material and the like of the gas barrier layer are not particularly limited as long as the desired gas barrier property can be provided. Examples of the gas barrier layer include a gas barrier layer formed of an inorganic vapor deposition film, a gas barrier layer containing a gas barrier resin, and a gas barrier layer obtained by subjecting a layer containing a polymer compound (hereinafter, sometimes referred to as "polymer layer") to a modification treatment [ in this case, the gas barrier layer refers not only to a region modified by an ion implantation treatment or the like but also to a "polymer layer containing a modified region. And the like.
Among them, a thin layer having excellent gas barrier properties can be formed effectively, and therefore a gas barrier layer formed of an inorganic vapor deposition film or a gas barrier layer obtained by subjecting a polymer layer to a modification treatment is preferable. The gas barrier film may contain 2 or more of these gas barrier layers.
Examples of the inorganic vapor-deposited film include vapor-deposited films of inorganic compounds or metals.
Examples of the material of the vapor deposition film of the inorganic compound include:
inorganic oxides such as silicon oxide, aluminum oxide, magnesium oxide, zinc oxide, indium oxide, tin oxide, zinc tin oxide, and the like,
inorganic nitrides such as silicon nitride, aluminum nitride, titanium nitride, etc.,
inorganic nitrogen oxides such as inorganic carbide, inorganic sulfide, silicon oxynitride and the like,
Inorganic oxycarbide, inorganic carbonitride, inorganic oxycarbonitride, and the like.
Examples of the raw material of the metal vapor deposited film include aluminum, magnesium, zinc, tin, and the like.
They may be used alone or in combination of 1 or more than 2.
Among them, an inorganic vapor deposited film using an inorganic oxide, an inorganic nitride or a metal as a raw material is preferable from the viewpoint of gas barrier properties, and an inorganic vapor deposited film using an inorganic oxide or an inorganic nitride as a raw material is preferable from the viewpoint of colorless transparency. In addition, the inorganic vapor deposited film may be a single layer or a plurality of layers.
From the viewpoints of gas barrier properties and handleability, the thickness of the inorganic vapor deposited film is usually 1nm to 2000nm, preferably 3nm to 1000nm, more preferably 5nm to 500nm, still more preferably 40nm to 200 nm.
The method for forming the inorganic vapor deposited film is not particularly limited, and a known method can be used. Examples of the method for forming the inorganic vapor deposition film include PVD (physical vapor deposition) methods such as vacuum vapor deposition, sputtering, and ion plating, thermal CVD (chemical vapor deposition) methods, CVD methods such as plasma CVD and photo CVD, and Atomic Layer Deposition (ALD).
Examples of the gas barrier resin to be used in the gas barrier layer containing the gas barrier resin include resins that are resistant to permeation of oxygen or water vapor, such as polyvinyl alcohol or a partially saponified product thereof, ethylene-vinyl alcohol copolymer, polyacrylonitrile, polyvinyl chloride, polyvinylidene chloride, and polychlorotrifluoroethylene.
From the viewpoint of gas barrier properties, the thickness of the gas barrier layer containing the gas barrier resin is usually 1nm to 2000nm, preferably 3nm to 1000nm, more preferably 5nm to 500nm, still more preferably 40nm to 200 nm.
As a method for forming the gas barrier layer containing the gas barrier resin, there is a method in which a gas barrier layer forming solution containing the gas barrier resin is applied to a substrate or other layer, and the obtained coating film is dried appropriately.
The method of applying the solution for forming a gas barrier layer is not particularly limited, and methods listed as the method of applying the resin composition described above can be used.
The method for drying the coating film is not particularly limited, and the methods listed as the method for drying the coating film of the resin composition described above can be used.
Examples of the polymer compound used in the gas barrier layer obtained by modifying the surface of the polymer layer include silicon-containing polymer compounds, polyimide, polyamide, polyamideimide, polyphenylene ether, polyether ketone, polyether ether ketone, polyolefin, polyester, polycarbonate, polysulfone, polyether sulfone, polyphenylene sulfide, polyarylate, acrylic resin, alicyclic hydrocarbon resin, aromatic polymer, and the like.
These polymer compounds may be used singly or in combination of 1 or more than 2.
Among these polymer compounds, a silicon-containing polymer compound is preferable from the viewpoint of being able to form a gas barrier layer having more excellent gas barrier properties. Examples of the silicon-containing polymer compound include polysilazane compounds, polycarbosilane compounds, polysilane compounds, polyorganosiloxane compounds, poly (ethylenesilylene) compounds, and poly (ethylenesilylene ethynylene) compounds. Among them, polysilazane compounds are preferable from the viewpoint of forming a gas barrier layer having excellent gas barrier properties even when thin. By subjecting the layer containing the polysilazane compound to a modification treatment, a layer (silicon oxynitride layer) containing oxygen, nitrogen, and silicon as main constituent atoms can be formed.
The polysilazane compound is a polymer compound having a repeating unit containing a-Si-N-bond (silazane bond) in a molecule. Specifically, a compound having a repeating unit represented by formula (1) is preferable.
[ chemical 1]
The number average molecular weight of the polysilazane compound to be used is not particularly limited, but is preferably 100 to 50,000.
In the formula (1), n represents an arbitrary natural number.
Rx, ry and Rz each independently represent a non-hydrolyzable group such as a hydrogen atom, an unsubstituted or substituted alkyl group, an unsubstituted or substituted cycloalkyl group, an unsubstituted or substituted alkenyl group, an unsubstituted or substituted aryl group or an alkylsilyl group.
Among them, rx, ry and Rz are preferably a hydrogen atom, an alkyl group having 1 to 6 carbon atoms or a phenyl group, and particularly preferably a hydrogen atom.
As the polysilazane compound having the repeating unit represented by the formula (1), inorganic polysilazanes each having a hydrogen atom in Rx, ry and Rz, and organic polysilazanes each having at least 1 other than a hydrogen atom in Rx, ry and Rz may be used.
In the present invention, a polysilazane modified product may be used as the polysilazane compound. Examples of the polysilazane modified product include compounds described in Japanese patent application laid-open No. 62-195024, japanese patent application laid-open No. 2-84437, japanese patent application laid-open No. 63-81122, japanese patent application laid-open No. 1-138108, japanese patent application laid-open No. 2-175726, japanese patent application laid-open No. 5-238827, japanese patent application laid-open No. 6-122852, japanese patent application laid-open No. 6-306329, japanese patent application laid-open No. 6-299118, japanese patent application laid-open No. 9-31333, japanese patent application laid-open No. 5-345826, and Japanese patent application laid-open No. 4-63833.
Among them, as the polysilazane compound, perhydro polysilazane in which Rx, ry, and Rz are all hydrogen atoms is preferable from the viewpoints of easy availability and formation of an ion-implanted layer having excellent gas barrier properties.
Further, as the polysilazane compound, a commercially available product such as a glass coating material can be used as it is.
The polysilazane compound may be used alone or in combination of 1 or more than 2.
The polymer layer may contain other components in addition to the polymer compound described above within a range that does not hinder the object of the present invention. The other components may contain additives listed as components other than the above-mentioned component (A), component (B) and component (C).
Since a gas barrier layer having more excellent gas barrier properties can be formed, the content of the polymer compound in the polymer layer is preferably 50% by mass or more, more preferably 70% by mass or more.
The thickness of the polymer layer is not particularly limited, and is usually 20nm to 50 μm, preferably 30nm to 1 μm, more preferably 40nm to 500 nm.
The polymer layer can be formed, for example, by: the liquid in which the polymer compound is dissolved or dispersed in the organic solvent is applied to a substrate or other layer by a known coating method, and the resulting coating film is dried.
As the organic solvent, those listed as components other than the above-mentioned component (a), component (B) and component (C) can be used.
These organic solvents may be used alone or in combination of 1 or more than 2.
The coating method is not particularly limited, and methods listed as the method for coating the resin composition described above can be used.
The method for drying the coating film is not particularly limited, and the methods listed as the method for drying the coating film of the resin composition described above can be used.
The heating temperature is usually 80 to 150 ℃, and the heating time is usually tens of seconds to tens of minutes.
Examples of the method for modifying the surface of the polymer layer include ion implantation treatment, plasma treatment, ultraviolet irradiation treatment, and heat treatment.
As described below, the ion implantation treatment is a method of implanting accelerated ions into the polymer layer to modify the polymer layer.
The plasma treatment is a method of modifying a polymer layer by exposing the polymer layer to plasma. For example, the plasma treatment may be performed according to the method described in japanese patent application laid-open No. 2012-106421.
The ultraviolet irradiation treatment is a method of irradiating the polymer layer with ultraviolet light to modify the polymer layer. For example, the ultraviolet ray modification treatment may be performed according to the method described in Japanese patent application laid-open No. 2013-226757.
Among these gas barrier layers, a gas barrier layer obtained by subjecting a layer containing a silicon-containing polymer compound to an ion implantation treatment is preferable in that the surface of the polymer layer is not roughened, but can be efficiently modified into the interior thereof to form a gas barrier layer having more excellent gas barrier properties.
Examples of the ions to be implanted into the polymer layer include:
ions of rare gases such as argon, helium, neon, krypton, and xenon,
fluorocarbon, hydrogen, nitrogen, oxygen, carbon dioxide, chlorine, fluorine, sulfur, and the like,
ions of an alkane gas such as methane or ethane,
ions of olefin gases such as ethylene and propylene,
ions of diene gases such as pentadiene and butadiene,
ions of an alkyne gas such as acetylene,
ions of aromatic hydrocarbon gases such as benzene and toluene,
ions of a cycloalkane-based gas such as cyclopropane,
ions of cycloolefin gas such as cyclopentene,
ions of metals, ions of organosilicon compounds, and the like.
These ions may be used singly or in combination of 1 kind or more than 2 kinds.
Among them, ions of rare gases such as argon, helium, neon, krypton, and xenon are preferable because ions can be implanted more easily, and a gas barrier layer having more excellent gas barrier properties can be formed.
The ion implantation amount can be appropriately determined depending on the purpose of use of the gas barrier film (desired gas barrier property, colorless transparency, etc.), and the like.
Examples of the method of implanting ions include a method of irradiating ions (ion beam) accelerated by an electric field and a method of implanting ions (plasma ions) in plasma. Among them, the latter method of implanting plasma ions (plasma ion implantation method) is preferable from the viewpoint of being able to simply form the target gas barrier layer.
The plasma ion implantation method is performed, for example, by generating plasma in an atmosphere of a plasma generating gas containing a rare gas or the like, and applying a negative high-voltage pulse to the polymer layer, thereby implanting ions (cations) in the plasma into the surface portion of the polymer layer. More specifically, the plasma ion implantation method can be performed by a method described in WO2010/107018 pamphlet or the like.
The thickness of the region into which ions are implanted by ion implantation can be controlled by the type of ions, the applied voltage, the treatment time, and other implantation conditions, and is determined according to the thickness of the polymer layer, the purpose of use of the gas barrier film, and the like, but is usually 10nm to 400 nm.
The ion implantation was confirmed by elemental analysis measurement in the vicinity of 10nm from the surface of the polymer layer using X-ray photoelectron spectroscopy (XPS).
The method for producing the sealing sheet (γ) is not particularly limited. For example, the sealing sheet (γ) can be produced by replacing 1 sheet of the release film with a gas barrier film in the production method of the sealing sheet (β) described earlier.
Further, the sealing sheet (γ) may be produced by peeling 1 sheet of the release film after the production of the sealing sheet (β), and adhering the exposed adhesive layer to the gas barrier film. In this case, in the case where the sealing sheet (β) has 2 sheets of release films and the 2 sheets of release films have different release forces, it is preferable to peel the release film having a smaller release force from the viewpoint of operability.
As described above, the adhesive layer of the sealing sheet of the present invention is excellent in adhesive strength, colorless transparency and water vapor barrier property. Therefore, the sealing sheet of the present invention is suitable for optical applications such as sealing materials for light emitting devices such as organic EL elements.
3) Sealing body
The sealing body of the present invention is formed by sealing an object to be sealed using the sealing sheet of the present invention.
The term "sealed with the sealing sheet of the present invention" means that the release film constituting the sealing sheet of the present invention is removed to expose the adhesive layer, and the adhesive layer is adhered to the object to be sealed to cover the object to be sealed.
The sealing body of the present invention includes, for example, a sealing body including a substrate, an element (object to be sealed) formed on the substrate, and a sealing material for sealing the element, wherein the sealing material is an adhesive layer of the sealing sheet of the present invention.
The substrate is not particularly limited, and various substrate materials may be used. Particularly, a substrate material having high transmittance of visible light is preferably used. In addition, a material having high blocking performance against moisture and gas which may permeate from the outside of the element and having excellent solvent resistance and weather resistance is preferable. Specifically, examples of the gas barrier film include transparent inorganic materials such as quartz and glass, transparent plastics such as polyethylene terephthalate, polyethylene naphthalate, polycarbonate, polystyrene, polyethylene, polypropylene, polyphenylene sulfide, polyvinylidene fluoride, acetyl cellulose, brominated phenoxy resin, aromatic polyamides, polyimides, polystyrenes, polyarylates, polysulfones, and polyolefins.
The thickness of the substrate is not particularly limited, and may be appropriately selected in consideration of the transmittance of light and the performance of blocking the inside and outside of the element.
Examples of the object to be sealed include an organic EL element, an organic EL display element, a liquid crystal display element, and a solar cell element.
The method for producing the sealing body of the present invention is not particularly limited.
For example, in the case of the structure of the sealing sheet (α) of the present invention, the object to be sealed is sealed with the adhesive layer of the sealing sheet by attaching the adhesive layer to the object to be sealed. In the case of using a release film for the sealing sheet (α), the release film is removed after sealing.
In the case of the structure of the sealing sheet (β) of the present invention, the release film on one side of the sealing sheet (β) is removed, the gas barrier film is bonded to the exposed adhesive layer, and then the other side of the release film is removed, and the adhesive layer is bonded to the object to be sealed, whereby the object to be sealed is sealed with the adhesive layer of the sealing sheet.
In the case of the structure of the sealing sheet (γ) of the present invention, the release film is removed, and the adhesive layer is attached to the object to be sealed, whereby the object to be sealed is sealed with the adhesive layer of the sealing sheet.
The bonding condition for bonding the adhesive layer of the sealing sheet and the object to be sealed is not particularly limited. The bonding temperature is, for example, 23 to 100 ℃, preferably 23 to 80 ℃, more preferably 23 to 40 ℃. The bonding treatment may be performed while pressurizing.
In the present invention, a material having an uncured adhesive layer (a dried coating film of the resin composition of the present invention) may be used as the sealing sheet, and the uncured adhesive layer of the sealing sheet may be photo-cured after the uncured adhesive layer and the object to be sealed are bonded.
As the curing conditions at this time, the conditions described previously can be used.
The sealing body of the present invention is formed by sealing an object to be sealed with the sealing sheet of the present invention.
Therefore, in the sealing body of the present invention, the performance of the sealed object can be maintained for a long period of time.
Examples
Hereinafter, the present invention will be described in more detail with reference to examples. However, the present invention is not limited to the following examples.
Unless otherwise specified, parts and% in each case are mass basis.
In the following examples and comparative examples, the following were used as the modified polyolefin resin [ (A) component ], the compound having a cyclic ether group [ (B) component ], and the photo-cationic polymerization initiator [ (C) component ].
Modified polyolefin resin [ (A) component ]
Acid-modified alpha-olefin polymer [ trade name of Sanjing chemical Co., ltd.: unistone H-200, number average molecular weight: 47,000]
Compounds having cyclic ether groups [ (B) component ]
(1) Compounds having cyclic ether groups (B-1)
Dicyclopentadiene dimethanol diglycidyl ether [ trade name of ADEKA company: ADEKA RESIN EP-4088L, cyclic ether equivalent: 165g/eq, liquid at 25 DEG C
(2) Compounds having cyclic ether groups (B-2)
2-ethylhexyl oxetane [ manufactured by east asia Synthesis Co., ltd., trade name: next-212, cyclic ether equivalent: 226g/eq, liquid at 25 DEG C
(3) Compounds having cyclic ether groups (B-3)
Triglycidyl isocyanurate (trade name, manufactured by Nissan chemical industry Co., ltd.): TEPIC-FL, cyclic ether equivalent: 165-185g/eq, liquid at 25 DEG C
(4) Compounds having cyclic ether groups (B-4)
Hydrogenated bisphenol a type epoxy resin [ trade name of mitsubishi chemical company: YX8034, cyclic ether equivalent: 270g/eq, liquid at 25 DEG C
Photo cation polymerization initiator [ (C) component ]
(1) Photo cation polymerization initiator (C-1)
Triarylsulfonium salt [ San-Apro ltd., trade name: CPI-200K, anion: anions with hexafluorophosphate skeleton ]
(2) Photo cation polymerization initiator (C-2)
Triarylsulfonium salt [ San-Apro ltd., trade name: CPI-310B, anions: tetrakis (pentafluorophenyl) borate ].
Example 1
A resin composition (1) having a solid content of 27% was prepared by dissolving 100 parts of an acid-modified alpha-olefin polymer (A), 25 parts of a compound having a cyclic ether group (B-1), 0.1 part of a photo-cation polymerization initiator (C-1), 50 parts of a tackifier [ styrene-based monomer/aliphatic-based monomer copolymer resin (trade name: FTR6100, softening point 95 ℃ C. Manufactured by Mitsui chemical Co., ltd.) ] and 0.1 part of a silane coupling agent [ 8-glycidoxy-octyl trimethoxysilane (trade name: KBM4803, manufactured by Xinyue chemical Co., ltd.) ] in toluene.
The resin composition (1) was applied to a release treated surface of a release film (manufactured by LINTEC Corporation; trade name: SP-PET 382150), and the resulting coating film was dried at 100℃for 2 minutes to form an adhesive layer having a thickness of 20. Mu.m, and another 1 release film (manufactured by LINTEC Corporation; trade name: SP-PET 381031) was laminated thereonAnd separating from the treatment surface. Then, an ultraviolet irradiation device (EYE GRAPHICS Co., ltd., trade name: US 2-0801) was used<2>) At an illuminance of 200mW/cm 2 The light quantity was 200mJ/cm 2 The coating film is cured by irradiation with ultraviolet rays to obtain a sealing sheet (1).
Examples 2 to 4
Resin compositions (2) to (4) were prepared in the same manner as in example 1 except that the compound (B-1) having a cyclic ether group was used in the amounts shown in Table 1, and sealing sheets (2) to (4) were obtained using these resin compositions.
Example 5
A resin composition (5) was prepared in the same manner as in example 1 except that the compound (B-2) having a cyclic ether group was used instead of using the compound (B-1) having a cyclic ether group in example 1, and a sealing sheet (5) was obtained using the resin composition.
Example 6
A resin composition (6) was prepared in the same manner as in example 1 except that the compound (B-3) having a cyclic ether group was used instead of using the compound (B-1) having a cyclic ether group in example 1, and a sealing sheet (6) was obtained using the resin composition.
Examples 7 and 8
Resin compositions (7) and (8) were prepared in the same manner as in example 1 except that the photo-cationic polymerization initiator (C-1) was used in the amounts shown in Table 1, and sealing sheets (7) and (8) were obtained using these resin compositions.
Example 9
A resin composition (9) was prepared in the same manner as in example 1 except that the photo-cationic polymerization initiator (C-2) was used instead of using the photo-cationic polymerization initiator (C-1) in example 1, and a sealing sheet (9) was obtained using the resin composition.
Example 10
A resin composition (10) was prepared in the same manner as in example 1 except that the content of the tackifier was changed to 25 parts, and a sealing sheet (10) was obtained using the resin composition.
Comparative example 1
A resin composition (11) was produced in the same manner as in example 1, except that the acid-modified α -olefin polymer (a) was not used in example 1.
In addition, although an attempt was made to produce a sealing sheet using this resin composition in the same manner as in example 1, the sheet processability (film forming property) was low, and a sealing sheet could not be obtained.
Comparative example 2
A resin composition (12) was prepared in the same manner as in example 1 except that the compound (B-1) having a cyclic ether group was not used in example 1, and a sealing sheet (12) was obtained using the resin composition.
Comparative example 3
A resin composition (13) was produced in the same manner as in example 1 except that the compound (B-4) having a cyclic ether group was used instead of using the compound (B-1) having a cyclic ether group in example 1, and the photo-cationic polymerization initiator (C-1) was not used, and a sealing sheet (13) was obtained using the resin composition.
The sealing sheets (1) to (10), (12) and (13) obtained in examples 1 to 10 and comparative examples 2 and 3 were measured and evaluated as follows. The results are shown in table 1.
[ measurement of adhesive force ]
The release film of the sealing sheet having a width of 25mm was peeled off to remove 1 sheet, and the adhesive layer was exposed. The exposed adhesive layer was bonded to a polyethylene terephthalate film (manufactured by LINTEC Corporation, thickness: 50 μm, single-layer product). Then, the other release film of the seal sheet was peeled off, and the exposed adhesive was laminated on alkali-free glass (trade name: EAGLE XG, manufactured by Corning corporation) with a pressing roller, to prepare a test piece.
The test piece thus produced was subjected to 180 ° peel test at a temperature of 23 ℃ and a relative humidity of 50%.
In this peel test, in addition to the above test conditions, the test was conducted in accordance with JIS Z0237:2009, the adhesive force is measured.
[ measurement of Total light transmittance ]
The release film of the sealing sheet was peeled off to remove 1 sheet, and the adhesive layer was exposed. The sealing sheet was placed on soda lime glass (thickness: 1 mm) so that the exposed adhesive layer was opposed to the soda lime glass, and then, the sealing sheet was bonded at 23 ℃ using a laminator, thereby producing a test piece.
The total light transmittance of the test piece thus produced was measured using a total light transmittance measuring apparatus (product name: NDH-5000, manufactured by Nippon electric color industry Co., ltd.).
[ color measurement ]
The same test piece as that used in the total light transmittance was produced.
The color value defined by the CIE1976L a b color system was measured on the test piece produced according to JIS Z8781-4 (2013) using a spectrophotometer (product name: UV-3600, manufactured by Shimadzu corporation).
[ evaluation of yellow index ]
The release film of the sealing sheet was peeled off to remove 1 sheet, and the adhesive layer was exposed. The sealing sheet was placed on soda lime glass (thickness: 1 mm) so that the exposed adhesive layer was opposed to the soda lime glass, and then, the sealing sheet was bonded at 23 ℃ using a laminator, thereby producing a test piece.
The test piece thus produced was subjected to JIS K7373: 2006, measurement was performed using a spectrophotometer (product name: UV-3600 manufactured by Shimadzu corporation).
[ measurement of Water vapor Transmission Rate ]
The water vapor permeability of the sealing sheet was measured using a water vapor permeability meter (manufactured by SYSTECH INSTRUMENTS Ltd., product name: LYSSY L80-5000) under an environment having a temperature of 40℃and a relative humidity of 90%.
TABLE 1
The following can be seen from table 1.
The sealing sheets (1) to (10) formed by using the resin compositions (1) to (10) containing the component (A), the component (B) and the component (C) have excellent adhesive strength under the conditions that the temperature is 23 ℃ and the relative humidity is 50% (examples 1 to 10).
The sealing sheets (1) to (10) have high total light transmittance, and the absolute values of a and b and the yellow index YI are small, and the sealing sheets are excellent in colorless transparency.
In addition, the sealing sheets (1) to (10) are excellent in water vapor blocking property.
On the other hand, the resin composition (11) containing no component (a) had low sheet processability (film formability), and a sealing sheet (comparative example 1) could not be obtained.
Further, the seal sheets (12) and (13) formed using the resin composition (12) containing no component (B) and the resin composition (13) containing no component (C) had poor adhesive strength at a temperature of 23 ℃ and a relative humidity of 50% (comparative examples 2 and 3).